PENGARUH KARAKTER MANDIRI TERHADAP KEPERCAYAAN DIRI DALAM BELAJAR PADA SISWA KELAS III SDN KEDOYA UTARA 04 - Fitria Rosmi; Intan Maharani (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
The student learning process is not only determined by cognitive abilities, but is also greatly influenced by personality factors, one of which is an independent character. An independent character has an important role in helping students develop selfconfidence in learning. Students who have an independent character tend to be more confident in making decisions, completing tasks without relying on others, and are able to face learning challenges. However, there are still many students who lack independence and are unsure of their own abilities in learning. This study aims to determine whether there is an influence of an independent character on selfconfidence in learning in grade III students of SDN Kedoya Utara 04. This study uses a quantitative approach with a survey method. The instrument used is a Likert scale questionnaire that covers daily, weekly, and monthly activities. The number of respondents in this study was 64 students. Data analysis was carried out by a simple linear regression test through the F test. The results showed a significance value of 0.000 and F count of 31.824, while F table was 4.03. Because F count > F table and significance < 0.05, then H₀ is rejected and Hₐ is accepted. Thus, there is a significant influence between independent character and self-confidence in learning of third grade students of SDN Kedoya Utara 04.